On the Roles of Wheat Endosperm ADP-Glucose Pyrophosphorylase Subunits - Ferrero, Danisa M. L.; Asencion Diez, Matias D.; Kuhn, Misty L.; Falaschetti, Christine A.; Piattoni, Claudia V.; Iglesias, Alberto A.; Ballicora, Miguel A. (Frontiers in Plant Science, 2018)
The ADP-glucose pyrophosphorylase from wheat endosperm controls starch synthesis in seeds and has unique regulatory properties compared to others from this family. It comprises two types of subunits, but despite its importance, little is known about their roles. Here, we synthesized de novo the wheat endosperm ADP-glucose pyrophosphorylase small (S) and large (L) subunit genes, heterologously expressed them in Escherichia coli, and kinetically characterized the recombinant proteins. To understand their distinct roles, we co-expressed them with well characterized subunits from the potato tuber enzyme to obtain hybrids with one S subunit from one source and an L subunit from the other. After kinetic analysis of these hybrids, we concluded that the unusual insensitivity to activation of the wheat endosperm enzyme is caused by a pre-activation given the L subunit. In addition, the heat stability and sensitivity to phosphate are given by the S subunit.